SOSIALISASI PROGRAM PROFIL PELAJAR PANCASILA PADA SD YPK ERMASU MERAUKE - Day, Wa Ode Siti Hamsinah; Syukron, Nurkholis; Ismail, My; Fredy, Fredy (LPPM Universitas Flores, 2024)
This devotion program aims to increase students’ and teachers’ knowledge and understanding of the Profil Pelajar Pancasila policy program. Profil Pancasila Pancasila policy program is a concept that involves Pancasila as an ideology of the state for the students. This service aims to provide socialization to the teachers and the students about Profil Pelajar Pancasila and give them an understanding of the implementation of the program every day. The method used in this service is delivering Profil Pelajar Pancasila's material through lectures, forum group discussions and direct practical activities. Teachers and Students will be given an understanding of the importance of the Profil Pelajar Pancasila Policy Program and the positive impact they will get if they adopt this ideology. The expected results of this service are an increase in teachers’ and students' knowledge about Profil Pelajar Pancasila and a strengthening in ideology that leads to guiding the student's life as a citizen in Indonesia. With this socialisation, it is hoped that students and teachers will become agents of change who can influence their peers and the community to adopt Pancasila as their ideology. In addition, this dedication is also expected to increase the nationalism of educators, parents and students in building a Profil Pelajar Pancasila ideology in schools and the surrounding environment. In conclusion, after this service has been done, students of SD YPK Ermasu Merauke understand and implement the importance of Profil Pelajar Pancasila in daily life.